Distal embedding as a technology innovation network formation strategy - Harold Paredes-Frigolett; Andreas Pyka (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2012)
Although the area of innovation economics dates back to the early twentieth century with the seminal contributions of Schumpeter (1911), it is only recently that governments have understood the role of a comprehensive approach towards public sector economics that puts innovation systems in the eye of public policy decision makers. Although well researched in academia in recent years, the role that innovation networks play in driving successful processes of innovation and entrepreneurship has been less understood by policy makers. Indeed, so far public policy makers have been concerned with the macro level of public policy in a way that has been rather disconnected from the meso level of innovation networks. Not surprisingly, overall strategies for innovation network formation have not been on the radar screen of public policy. The academic community, on the other hand, has been devoting more attention to the study of innovation networks in an attempt to understand the role they play as a catalyst of innovation and entrepreneurship. By and large in the research community, the process of innovation network formation has been left rather unattended. Indeed, the question of how these networks are formed and what strategies can be developed to ignite processes of innovation network formation has been largely absent from the academic debate. In this article, we make a contribution in this area and present distal embedding as one of three generic innovation network formation strategies. We also show why distal embedding'' is particularly well suited for emerging regions of innovation and entrepreneurship. Our contributions lie at the macro-meso interface and can shed light on public policy at the macro level aiming to have a direct impact at the meso level of innovation network formation.
urn:nbn:de:bsz:100-opus-7259
Keywords: 330; entrepreneurship; innovation networks; innovation network strategy formation; Unternehmer; Innovation; Unternehmensnetzwerk; Theorie; Israel